Revealing Indonesia through The Grief of Film: Marlina The Murderer in Four Acts - Fitriansal, Fitriansal (Universitas Cokroaminoto Palopo, 2025)
This study is based on qualitative research using the grief of film model in the five stages of Kubler-Ross. The aim is to unveil the grief of the film